SMART CARD BASED RECOGNITION SYSTEM "SMART HEALTH CARE" - Kristian Manihuruk (Jurnal Sistem Komputer, 2005)
Person's medical record information is one factor that determines the quality ofservice provided by central health care services to patients and, therefore, thismedical record information should always be there when needed. Confidentiality ofmedical record information is essential arena this information to explain the specialrelationship between patient and physician, who must be protected from leakage inaccordance with the code of medical ethics and the applicable legislation.This research aims to design a medical record system in accordance with theprovisions of Indonesia's medical records, ensure data security, portability by theowner, maximize health services for the emergency condition, and accelerate andimprove health service outpatient at a hospital or reference between hospitals. Toachieve these objectives, the authors will study the government regulations regardingmedical records, medical records system to know some using existing smartcardcountryof other countries to obtain medical smartcard system is the safest amongthese systems.